The Knowledge and Practice of Women Referred to the Health Centers Affiliated to Ahvaz' University of Medical Sciences on Breast Cancer and its Screening Methods - Afsaneh Alivand; Abdolhassan Doulah; Saeed Ziagham (Mashhad University of Medical Sciences, 2016)
Background & aim: Breast cancer is recognized as the most common type of cancer among Iranian women. Cancer screening and early diagnosis are among the most effective strategies to reduce the associated mortality and healthcare costs. Accordingly, the aim of this study was to investigate the level of knowledge and practice of breast cancer screening among women referred to hospitals affiliated to Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran. Methods: This cross-sectional, descriptive, analytical study was conducted on 70 women, referred to hospitals affiliated to Ahvaz University of Medical Sciences. The subjects were randomly selected via cluster sampling. For data collection, a questionnaire consisting of three parts, i.e., demographic, knowledge, and practice information, was used. For statistical analysis, Chi-square test was performed, using SPSS version 16. Results: The results showed that the majority of the patients were married and within the age range of 35-39 years. Most participants (42.9%) had poor knowledge of breast self-examination. Based on the findings, knowledge and practice of breast cancer screening were not significantly associated with age or educational level. Nevertheless, a significant relationship was found between the knowledge level and marital status of the subjects. Conclusion: Based on the findings, women's knowledge and practice of breast cancer screening were quite poor. Therefore, it is suggested to promote the current level of knowledge in order to prevent delayed diagnosis.